Enhancing permeability and porosity of ceramic shells for investment casting through pre-wetting. Issue 16 (December 2021) - O'Sullivan, Noel; Mooney, Joseph; Tanner, David
Abstract: In this study, a method known as pre-wetting is applied between the multilayer ceramic investment casting shells to enhance porosity and permeability while sustaining flexural strength. Pre-wetting consists predominately of an aqueous silica binder that improves inter-coat bonding in complex areas. Porosity is developed where the pre-wetting is applied due to the evaporation of the aqueous phase. Results indicate that as porosity increases, both green and fired flexural strength reduce on average by 8.7 - 15.6 % and 18.7 - 28.5 %, respectively, whereas hot strength is increased by 20 - 25 %. Permeability increased by a factor of two when pre-wetting was applied between intermediate coatings and displayed a stepwise increase in intrusion volume in the high-pressure regime through mercury intrusion porosimetry. X-ray microtomography coupled with pore network modelling provided a validation of the increase in the permeability constant. Gas adsorption methods revealed the presence of micropores through the alpha-s method when bilayers of pre-wetting solution were applied.